Effect of studying cell biology with a virtual cell: a comparison between Canada and Costa Rica and between presential and distance education (UNED Research Journal, 2010)
When compared with education in industrialized countries, Latin American education often seems outdated and inferior. However, widespread use of computers might tend to reduce regional differences. To determine whether learning would be different when the same digital material was used in Canada (industrialized country) and Costa Rica (with an economy based on ecotourism and agriculture), we used Cellule, an interactive multimedia with animations, text and sound, for teaching basic cell biology. A total of 96 students from Canada and Costa Rica used the multimedia. We evaluated their opinion on the multimedia using questionnaires. We found no significant differences by country, or by the mode of teaching (in real classrooms or through distance learning). Cellule is an excellent multimedia for teaching basic cell biology, in both industrialized and Latin American countries.
Keywords: Learning with computers; multimedia; virtual laboratories; digital cell; education in industrialized and non-industrialized countries.